Pengembangan Sistem Frequently Asked Questions (FAQ) pada Universitas Udayana Berbasis Ontology - Ananda, Ngurah Kelvin Febryanta Lila; Karyawati, Anak Agung Istri Ngurah Eka; Pramartha, Cokorda Rai Adi; Kadyanan, I Gusti Agung Gede Arya (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 4 (2025): JELIKU Volume 13 No 4, May 2025DO - 10.24843/JLK.2025.v13.i04.p07, 2025)
Digital transformation in public services is a strategic step to enhance organizational efficiency and responsiveness in meeting user needs. This study aims to develop an ontology-based Frequently Asked Questions (FAQ) system to provide accurate, relevant, and easily accessible information at Udayana University. The system is designed using an ontology-based approach that represents relationships between concepts in a structured manner, combined with the Sentence Transformer (Sentence-BERT) method to understand variations in language and sentence structures in user queries. The study results show that the development of the ontology-based FAQ system successfully represents information in a structured and relevant manner according to user needs. The evaluation indicates a usability score of 90% and a usefulness score of 88.57% , reflecting a high level of user acceptance and system benefits. Out of 20 questions tested, the system correctly answered 16 questions , achieving an accuracy rate of 80%. Overall, this ontology-based FAQ system effectively meets user needs by providing relevant, accurate, and efficient answers while reducing the workload of administrative staff. The system has significant potential to support more comprehensive information services at Udayana University.